Peta Batimetri Danau Rawapening - Soeprobowati, Tri Retnaningsih (Bioma : Berkala Ilmiah Biologi, 2012)
Lake has an important function as source of water;  maintain biodiversity; source of protein; manage toxicity; device to reduce river flooding; source  of groundwater; device climate; transportation and touris;  medium; and for cultural and religion activities. Semi natural lake of Rawapening has function for hydroelectricity power, irrigation for agriculture, fisheries, and tourism. For maintaning those functions, lake batimetric map is required for limnological study as well as for basic informasi for development lake management. However, there is no batimetric map of Rawapening Lake after1976  lake’s sketch by Goltenboth. Therefore, this survey was conducted in order to update batimetric map of Rawapening. On August 16th, 2008, echosounding was donecfross section and lake edge every 30 second. Recorded data on the GPS then interpolated to the lake depth form in every dot of echosounding.The deepest part of Rawapening Lake was 18 metres, around Bukit Cinta spring. Comparing to Goltenboth sketch, the Rawapening Lake depth was not quite change. North West part of the lake remain has 2-4.7 metres depth. However, based on sedimentation rate, the shallowness lake was very sharply, and predicted that in 2021 Rawapening Lake will full of sediment. Maintaning lake depth is a must to maintain lake’s function.   Key words: batimetri, Danau Rawapening, limnologi